Dampak Sarapan Sehat terhadap Konsentrasi dan Daya Tahan Tubuh Anak - Yoselina, Prima; Diah Anggita, Kheniva; Hasmita, Hasmita (Pustaka Galeri Mandiri, 2025)
Breakfast is the most important thing for school children in during growth and development. Breakfast habits in the morning can affect students' health, impacting their attendance at school and academic achievement. This study aims to determine the relationship between breakfast habits and student learning achievement. This descriptive study uses a cross-sectional approach in grade VII students of SMPN 4 VII Koto Sungai Sarik, Padang Pariaman Regency. The sample in this study uses the purposive sampling method to obtain a sample of 25 students. The data analysis used the chi-square test (p<0.05) using a questionnaire. The data were analyzed univariate and bivariate. The study results showed that the breakfast habits of students were generally less than 15 students (60%) and the concentration of students was less than as many as 14 students (56%). There was a significant relationship between breakfast habits and students' learning concentration with a value of p=0.04. Getting children used to breakfast, will increase the child's concentration on learning and the child's achievement will increase by itself